2007
DOI: 10.1136/bjsm.2007.040915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forward shoulder posture on pulmonary capacities of females

Abstract: Effect of forward shoulder posture on pulmonary capacities of women ERV, expiratory residual volume; FSP, forward shoulder posture; FVC, forced vital capacity; VC, vital capacity. Data are mean (SD).ERV, expiratory residual volume; FSP, forward shoulder posture; FVC, forced vital capacity; VC, vital capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…43 The aforementioned studies hence provide evidence of an association between FHP and rounded shoulders, 5,52 between FHP and thoracic kyphosis, 27,46 and between rounded shoulders and thoracic kyphosis. 19,25,26 To the best of our knowledge, only 4 papers were found that best supported the objective of this review. As can be observed in Tables 1 and 2, there is heterogeneity in the methods employed by these studies to observe posture; thus, we could not reach a definitive conclusion regarding the cause of FHP, FSP, or thoracic kyphosis, that is, what happens first among the 3 and what happens next.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…43 The aforementioned studies hence provide evidence of an association between FHP and rounded shoulders, 5,52 between FHP and thoracic kyphosis, 27,46 and between rounded shoulders and thoracic kyphosis. 19,25,26 To the best of our knowledge, only 4 papers were found that best supported the objective of this review. As can be observed in Tables 1 and 2, there is heterogeneity in the methods employed by these studies to observe posture; thus, we could not reach a definitive conclusion regarding the cause of FHP, FSP, or thoracic kyphosis, that is, what happens first among the 3 and what happens next.…”
Section: Discussionmentioning
confidence: 91%
“…51 FSP can be associated with FHP, 52 increased thoracic kyphotic posture, 19,25,26 or both 12,15 (Table 3). The scapula has been found to be anteriorly tilted, downwardly rotated, and protracted during elevation of the arm in persons with FHP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations